2012
DOI: 10.1016/j.jnci.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled dermoglandular flap reconstruction following breast conserving surgery

Abstract: Following central quadrantectomy BCS for small centrally located breast cancer, a pedicled dermoglandular flap from the upper outer quadrant is a good reconstructive option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, the scoring system in each methodology widely varied, such as 0% to 100% satisfaction, acceptable versus unacceptable, and excellent/good/satisfactory/poor 15, 29, 38, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59. The only standardization involved in methodology was the 5 parameters that were used in the cosmesis assessment: breast shape, symmetry, scars, nipple areola complex position and shape, and postirradiation sequelae 15, 29, 38, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59. The differences in the methodology diminish the possibility of establishing a meaningful comparison across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the scoring system in each methodology widely varied, such as 0% to 100% satisfaction, acceptable versus unacceptable, and excellent/good/satisfactory/poor 15, 29, 38, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59. The only standardization involved in methodology was the 5 parameters that were used in the cosmesis assessment: breast shape, symmetry, scars, nipple areola complex position and shape, and postirradiation sequelae 15, 29, 38, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59. The differences in the methodology diminish the possibility of establishing a meaningful comparison across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In those patients, early complications affected more frequently the breast with cancer than in the healthy breast, as infection, seroma formation and wound dehiscence, due to the more complex surgical approach and the more extensive surgery (including axillary SNB or complete axillary dissection -three levels). However, local complications at the cancer site do not negatively influences delivery of adjuvant treatment as reported by most studies comparing oncoplastic versus conservation alone, showing no difference in surgical complications between the two groups [67].…”
Section: Oncoplastic Surgerymentioning
confidence: 80%
“…Among the full range of oncoplastic techniques, there are two fundamentally different approaches: volumereplacement procedures, which combine resection with immediate reconstruction by using local flaps (glandular, fasciocutaneous and latissimus dorsi miniflaps); and volume-displacement procedures, which combine resection with a variety of different breast reduction and reshaping techniques, according to the location of the tumor. Among the all choices of oncoplastic techniques, there are two fundamentally diverse approaches: volume-replacement procedures, which match resection with immediate reconstruction by using local flaps (glandular, fasciocutaneous and latissimus dorsi miniflaps); and volume-displacement procedures, which combine resection with different breast reduction and reshaping techniques, based on the site of the tumor [67]. Both approaches may be performed in case of synchronous multicentric cancers according to tumor size and location and breast size.…”
Section: Oncoplastic Surgerymentioning
confidence: 99%
“…Zaha et al 26 noted that fat necrosis occurred in 5.2% of patients and these patients were treated conservatively. Khafagy et al 27 reported fat necrosis incidence rate of 6.67% with no seroma. Two patients (8.3%) in our study group II developed epigastric incisional hernia for whom a mesh hernioplasty was performed with complete disconnection of the omental flap that was intact and viable.…”
Section: Discussionmentioning
confidence: 98%